Mapping potential erosive zones in a Brazilian watershed: towards sustainable territorial planning - Guerrero, João Vitor Roque; Mataveli, Guilherme Augusto Verola; Lorandi, Reinaldo; Lollo, José Augusto di; Gomes, Alberto; Chaves, Michel; Moschini, Luiz Eduardo; Nunes, Fabrizia Gioppo (Revista do Departamento de Geografia, 2023)
Soil erosion is one of the greatest environmental problems in the 21st Century, mainly due to the economic, social, and environmental damages caused worldwide. Brazil is inserted within this context, where the implementation of strategies to support territorial planning aimed at soil conservation is urgently required. Thus, this work aimed to use geoenvironmental cartography techniques to map the potential erosive zones at the Gouveia stream watershed (Brotas, Brazil) based on geographic data systematized by geoprocessing. Parameters of geology, pedology, terrain shape, terrain slope, land use, and land cover were used and systematized in a GIS environment through mathematical operations and fuzzy inference to map the potential erosive zones. The results indicate that 63% of the basin consists of “High” and “Very High” potential areas for the erosion process, which requires an urgent need to implement management strategies and sustainable territorial planning. This approach can potentially contribute to the decision-making process in the study area and be applied in other watersheds worldwide.